The Peculiarities of the Reform of Local Self-Government: Examples of Ukraine, Latvia, and Poland - Karvatska, Svitlana (Studia Regionalne i Lokalne, 2023)
The article considers the peculiarities of local government reform based on the examples of Ukraine, Poland, and Latvia. It is substantiated that the Ukrainian vector of European integration requires the implementation of the principles of deconcentration, decentralisation, and subsidiarity in the local governance systems. It is indicated that regional disproportions in the development of the territory of Ukraine, the inability to implement the reform on the ground in specific administrative-territorial units, the spread of corruption schemes – all these are the consequences of an ineffective model of local self-government and public administration of regional development, inherited from the Soviet system, which requires fundamental changes. Broad powers for sub-regional units characterise the Pol- ish model of the administrative-territorial structure. However, this model is underpinned by a high level of political activity and community self-awareness. The Latvian experience of decentralisation of power emphasises the basic principle of success: the volunteer approach to the reform’s implementation. In conclusion, it is proved that for the successful implementation of the Ukrainian local self-government reform, the following factors are necessary: firstly, the victory of Ukrainian armed forces against the military aggression of Russia; secondly, the elaboration of a legal framework for the development of local self-government and the support of society; thirdly, qualified personnel ca- pable of continuing the implementation of the local self-government reform.
Keywords: public administration, local self-government, decentralisation of power, territorial community, European integration